Optimizing Profitability: The Role of Working Capital and Accounts Receivable Turnover - Bagus Setiawan; Desy Arigawati; Nadia Rista (Goodwood Publishing, 2026)
Purpose: This study investigates the effect of working capital turnover and accounts receivable turnover on profitability, measured by Return on Assets (ROA), in consumer goods manufacturing firms listed on the Indonesia Stock Exchange during the 2021–2024 period. Research Methodology: A sample of 47 companies was selected through purposive sampling using secondary data from published financial reports. The analysis applies descriptive statistics, correlation, and multiple regression techniques to assess the relationship between these variables. Results: The findings reveal that both working capital turnover and accounts receivable turnover have a significant impact on profitability when considered jointly. Individually, working capital turnover has a positive and significant effect on ROA, while accounts receivable turnover shows no significant influence. Conclusions: This study concludes that working capital turnover significantly improves profitability, while accounts receivable turnover has no significant effect. However, managing both working capital and accounts receivable turnover together can positively impact overall financial performance. Limitations: This study is limited to consumer goods manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period, which may not fully represent other sectors. Contributions: The study contributes to understanding the importance of efficient working capital management for profitability, providing insights for managers to optimize financial performance.